Neither here nor there or always here and there? Antipodean reflections on economic geography. (July 2013) - Wray, Felicity; Dufty-Jones, Rae; Gibson, Chris; Larner, Wendy; Beer, Andrew; Heron, Richard Le; O'Neill, Phillip
This paper emerged from discussions held over a two-day symposium hosted by the University of Western Sydney and the Institute of Australian Geographers in December 2011. Drawing on contemporary themes in economic geography around postcolonial theory and a concern with the histories of the sub-discipline, the symposium sought to triangulate these discourses using Raewyn Connell's (2006, 2007a, 2007b) concept of 'Southern Theory' as a means of beginning a process of critical reflection about the types of economic geographies that are produced from and in the 'Antipodes'. After introducing these debates and presenting a critical reflection on how Connell's Southern Theory potentially provides a useful means of bringing them into conversation, the paper presents five considerations from geographers who have made significant contributions to contemporary economic geography understandings, drawing on, in various ways, their Antipodean positionality. The paper assesses to what extent are Antipodean economic geography knowledges: (i) unique and embedded in specific conditions and events, (ii) inexorably tied to other economic geographical knowledges produced elsewhere and (iii) how Antipodean economic geography knowledges have been exported and assembled within and beyond the discipline of geography.